Efekty i atmosfery jako równoprawne środki budowania narracji filmowej w kinie głównego nurtu - Malwina Czajka-Jaworek (Studia Filmoznawcze)
In the existing literature on the subject, there is a prevailing belief that an increasing number of films are emerging in which the boundary between the soundtrack and the musical score is becoming increasingly blurred (L. Greene & D. Kulezic-Wilson, 2016; J. Napieralska, 2012). Advances in sound recording and playback technologies have enabled the construction of cinematic narratives that utilize all the possibilities offered by the auditory layer elements. Walter Murch, an American film editor and sound designer, together with a group of collaborators, played a key role in the establishment of multichannel sound standards and the spatialization of the auditory sphere. Digitization transformed the technical role of the sound engineer into that of a sound designer, who could focus on the artistic potential of their work and explore new creative solutions. In this article, the author seeks to verify these hypotheses by asking to what extent mainstream cinema—as a system—has indeed internalized the autonomy of sound design. To this end, an analysis is conducted of the auditory layer in films recognized by the Academy of Motion Picture Arts and Sciences in the Best Sound category between 2012 and 2023, comparing this category with others, such as Best Music and Best Editing. In testing the hypothesis of the equivalency of the sound and music tracks, the author focuses on a quantitative analysis of the presence of music in these films, as well as the ways in which non-musical sounds are utilized as expressive means conveying additional meanings. Foley, ambience and sound effects can all serve as equally significant tools in constructing the narrative. Films such as Joker (2018), Mad Max: Fury Road (2015), Sound of Metal (2019), Dune (2022), and Top Gun: Maverick (2022) illustrate this point. The analysis reveals that, while music continues to occupy significant screen time and it becomes increasingly difficult to distinguish music from sound effects in the mixed auditory layers of films, sound design plays a crucial role in shaping the final outcome of the work.